‘Ante omnia, fratres carissimi, diligatur Deus, deinde proximus’: Herman/Judah’s Opusculum de conversione sua Re-examined - Hames, Harvey J. (Conﬂict and Religious Conversation in Latin Christendom: Studies in Honour of Ora Limor, 2014)
Keywords: 👤 hermann of cologne

The Conversion of Herman the Jew: Autobiography, History, and Fiction in the Twelfth Century - Schmitt, Jean-Claude (University of Pennsylvania Press, 2012)
Keywords: 👤 hermann of cologne

Me peperit ecclesia mater. Einige Bemerkungen zur Selbstdarstellung Hermanns von Köln in seinem Opusculum de conversione sua - Gäbe, Sabine (Analecta Praemonstratensia, 2000)
Looking at the Opusculum from a literary studies perspective (form, stylizing, stereotyped attitudes, intention, reader’s point of view) one arrives at the following results: The descriptio historiae consists of a continuous description of the internal, spiritual, and intellectual struggle of the autobiographical ego. Individual experiences of his life are only reported in so far as they are important for the progression of conversion. „Historical Persons“ mentioned in the text do not have their own personality: Jews are stylized as adversaries of the conversion (according to the stereotyped attitudes stemming from the theological tradition). Christians, however, are made into role models. The identity of the autobiographical writer is the identity of an ordained Christian priest. His former Jewish identity is portrayed as „non-identity“. The intention of the work is not to be, as it was assumed in the past, a defence against the reproach that the conversion took place for opportunistic reasons. Nor is it an attempt to respond with anti-Semitic comments to latent hostile feelings against the former Jew. On the contrary, the intention is to show Christian readers an example of how to part Jews from their „hardening“ and win them for Christianity by gentleness and charity. The work attempts, as the second Crusade quickly approaches (among other things) to support efforts that defend Jews from encroachments.
Keywords: 👤 hermann of cologne

The ideology of reform and changing ideas concerning Jews in the works of Rupert of Deutz and Hermannus quondam Iudeus - Abulafia, Anna Sapir (Christians and Jews in Dispute: Disputational Literature and the Rise of Anti-Judaism in the West (c. 1000-1150), 1998)
Keywords: 👤 hermann of cologne

Les dimensions multiples du voir. Les rêves et l'image dans l'autobiographie de conversion d'Hermann le Juif au XIIe siècle - Schmitt, Jean-Claude (Micrologus: Natura, scienze e società medievali / Nature, Sciences and Medieval Societies, 1998)
Keywords: 👤 hermann of cologne

Zweifel an der Gleichsetzung des Propstes Hermann von Scheda mit dem jüdischen Konvertiten Hermann von Cappenberg - Horstkötter, Ludger (Analecta Praemonstratensia, 1995)
Keywords: scheda; 👤 hermann of cologne

La memoire des Prémontrés. A propos de la "Autobiographie" du Prémontré Hermann le Juif - Schmitt, Jean-Claude (La Vie quotidienne des moines et chanoines réguliers au Moyen Age et temps modernes: Actes du Premier Colloque International du L.A.R.H.C.O.R. Wrocław-Książ, 30. nov. - 4. dec. 1994, 1995)
Keywords: 👤 hermann of cologne

Hermannus Judaeus's Opusculum: in defence of its authenticity - Kleinberg, Aviad M. (Revue des Etudes Juives, 1992)
Keywords: 👤 hermann of cologne

Ist Hermann von Schedas Opusculum de conversione sua eine Fälschung? - Lotter, Friedrich (Aschkenas: Zeitschrift für Geschichte und Kultur der Juden, 1992)
Keywords: 👤 hermann of cologne

Hermann's Opusculum de conversione sua: truth or fiction? - Saltman, Avrom (Revue des études juives, 1988)
Keywords: 👤 hermann of cologne

Hermann von Scheda, Opusculum de conversione sua. Ein Beitrag zur jüdisch-christlichen Auseinandersetzung im Mittelalter - Drabek, Anna Maria (Kairos: Zeitschrift für Religionswissenschaft und Theologie, 1979)
Keywords: 👤 hermann of cologne

Hermannus, quondam Iudaeus, praepositus in Scheida - Valvekens, Johannes B. (Analecta Praemonstratensia, 1965)
Keywords: 👤 hermann of cologne